Zweikampf im Wattenmeer : Wird die heimische Miesmuschel verdrängt? - Damm, Ulrich; Neudecker, Thomas (2006)
Since a couple of years, the introduced Pacific oyster (Crassostrea gigas) is spreading out in the Wadden Sea off the German North Sea coast where it competes with the native blue mussel (Mytilus edulis). First catches of the new species have now been observed in fishing surveys.